β-Ionone reactions with ozone and OH radical: Rate constants and gas-phase products - Forester, Crystal D.; Ham, Jason E.; Wells, J. Raymond (Atmospheric environment (1994), 2007)
The bimolecular rate constants, k OH + β -ionone (118±30)×10 −12 cm 3 molecule −1 s −1 and k O 3 + β ‐ ionone , (0.19±0.05)×10 −16 cm 3 molecule −1 s −1, were measured using the relative rate technique for the reaction of the hydroxyl radical (OH) and ozone (O 3) with 4-(2,6,6-trimethyl-1-cyclohexen-1-yl)-3-buten-2-one ( β-ionone) at 297±3 K and 1 atm total pressure. To more clearly define part of β-ionone's indoor environment degradation mechanism, the products of the β-ionone+OH and β-ionone+O 3 reactions were also investigated. The identified β-ionone+OH reaction products were: glyoxal (ethanedial, HC(=O)C(=O)H), and methylglyoxal (2-oxopropanal, CH 3C(=O)C(=O)H) and the identified β-ionone+O 3 reaction product was 2-oxopropanal. The derivatizing agents O-(2,3,4,5,6-pentafluorobenzyl)hydroxylamine (PFBHA) and N, O-bis(trimethylsilyl)trifluoroacetamide (BSTFA) were used to propose 2,6,6-trimethylcyclohex-1-ene-1-carbaldehyde as the other major β-ionone+OH and β-ionone+O 3 reaction product. The elucidation of this other reaction product was facilitated by mass spectrometry of the derivatized reaction products coupled with plausible β-ionone+OH and β-ionone+O 3 reaction mechanisms based on previously published volatile organic compound+OH and volatile organic compound+O 3 gas-phase reaction mechanisms. The additional gas-phase products observed from the β-ionone+OH reaction are proposed to be the result of cyclization through a radical intermediate.